2003
DOI: 10.1086/367689
|View full text |Cite
|
Sign up to set email alerts
|

An Obscured Radio Galaxy at High Redshift

Abstract: Perhaps as many as 10% of high-redshift radio galaxy ( ) candidates that are selected using an ultrasteep z 1 2 radio spectrum criterion fail to show optical emission (continuum, lines) in deep Keck exposures. Their parent objects are only detected in the near-IR and are probably heavily obscured and/or at very high redshift. To search for signatures of dust and help constrain the nature and redshifts of these "no-z" radio galaxies, we have conducted a program of submillimeter and millimeter observations. Here… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Miley & De Breuck 2008), meaning that samples selected in the above way may not be completely representative of high‐ z radio galaxies. Interestingly, it has been suggested that these ‘no‐line’ radio galaxies are very dusty, based on millimetre/submillimetre detections thereof (Reuland et al 2003b; Reuland 2005).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Miley & De Breuck 2008), meaning that samples selected in the above way may not be completely representative of high‐ z radio galaxies. Interestingly, it has been suggested that these ‘no‐line’ radio galaxies are very dusty, based on millimetre/submillimetre detections thereof (Reuland et al 2003b; Reuland 2005).…”
Section: Datamentioning
confidence: 99%
“…Shown in Fig. 6 is S 1.1 versus radio size for the AzTEC counterparts together with HzRGs that have been observed at 850 m using SCUBA (Archibald et al 2001; Reuland et al 2003b, 2004; Stevens et al 2003). SCUBA 850‐m flux densities have been scaled by 1/2.5 to extrapolate their 1.1‐mm flux densities.…”
Section: Comparison With Radio and Optical Propertiesmentioning
confidence: 99%
“…Reuland et al 2003a), or not located at the centre of the host galaxy (e.g. Quirrenbach et al 2001).…”
Section: Where Is the Agn?mentioning
confidence: 99%
“…This is supported by the number density evolution of quasars and radio galaxies (Wall et al 2005;Richards et al 2006a) being similar to the evolution of the star formation rate (SFR) density with redshift (e.g., Giavalisco et al 2004). Observations of significant farinfrared (IR) emission potentially suggest starbursts associated with high-z quasars and radio galaxies (e.g., Willott et al 2002;Reuland et al 2003;Beelen et al 2006) and indicate rapid growth of the host galaxy, likely fueled by mergers (Hutchings et al 2006;Hopkins et al 2006). Studies of the young stellar populations of radio galaxies also suggest merger-driven starbursts (Tadhunter et al 2005).…”
Section: Introductionmentioning
confidence: 99%